Analisis Sosiologi Sastra Cerpen Penthouse 2601 Karya Djenar Maesa Ayu dan Implikasi Pembelajaran Bahasa Indonesia - Resvya Noer Fauzy; Diena San Fauziya (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Short stories are part of a literary genre that describes the environment. One of the important things in short stories is how the author's events and thoughts can be expressed well so that they can be understood and enjoyed well by readers. To find information contained in short stories in more depth, research can be done in the form of analysis. The aim of this research is to examine the content of the short story entitled "Penthouse 2601" by Djenar Maesa Ayu using a literary sociology approach. In literary sociology, literary works are considered as a reflection of society's life which cannot be separated from consideration of fictional elements and social aspects of society's life. The research method used in this research is a qualitative descriptive research method. By using listening and taking notes as a data collection technique. The results of this research show that in the short story entitled "Penthouse 2601" there are social aspects and cultural aspects. This research can have implications for Indonesian language learning, especially at the Senior High School (SMA) level